The role of municipal government in forming social security - Leszczyński, Marek (Polityka i Społeczeństwo, 2023)
The dynamics of economic, political and social changes constantly poses new threats to the existence and creative development of entities (public as well as human communities). The state remains the main entity that is responsible for creating the basics of security, yet it is crucial to study the ways and methods of forming social security for local communities. Under the approved political system, a significant role in ensuring security is ascribed to municipal governments and local governments’ institutions. Of key importance are efficiency and effectiveness in functioning of the local authorities as they greatly determine the citizens’ standard of living . Furthe rmore, an important area is the cooperation of local governments with entities responsible for social security (the entities belonging, among others, to the National Rescue and Fire Fighting System and the National Medical Emergency Services). This paper raises an issue of forming social security at a local level with the use of the logistical approach. An improvement in more effective provision of the social security is possible by using the logistical methods as well as social logistics philosophy. This philosophy aims to focus on achieving social goals and tends to attach less importance to the economics of its objectives. It is a relatively new approach that complements the traditional perception of military and business logistics. The constantly increasing numer of social threats makes one search for effective methods of reducing their effects and the help for people who are excluded or marginalised for various reasons. Moreover, the public administration, which plays important functions as serving administration, constantly needs to improve the ways of achieving goals connected to fulfilling its mission of a public character.